Post‐Flowering Drought Tolerance Using Managed Stress Trials, Adjustment to Flowering, and Mini Core Collection in Sorghum. Issue 1 (8th December 2016) - Upadhyaya, Hari D.; Dwivedi, Sangam L.; Vetriventhan, Mani; Krishnamurthy, L.; Singh, Shailesh Kumar
Abstract : Sorghum [ Sorghum bicolor (L.) Moench] crop in the semiarid tropics often suffers from post‐flowering drought stress, which causes substantial losses in grain yield and stover quality. This research was aimed at studying the yield response of sorghum mini core accessions to post‐flowering drought stress to identify drought‐tolerant sources for sorghum improvement. Mini core accessions were grouped based on days to 50% flowering (extra early, early, medium, late, and extra late) and evaluated in two post‐rainy seasons under managed drought stress and optimally irrigated conditions. Drought tolerance index (DTI), as a standard residual after removing the known contributory effects of flowering time and grain yield under optimum irrigation (yield potential) from the grain yield under drought, was used to segregate the genotypic responses to drought stress. The residual (or restricted) maximum likelihood analysis of data revealed significant genotypic variance (σ 2 g ) for days to 50% flowering, grain yield, and DTI (except in the extra late flowering group), in both the seasons and significant genotype × environment interactions for DTI in extra early to late flowering groups. On the basis of DTI, seven accessions, i.e., 'IS 14779', 'IS 23891', 'IS 31714', 'IS 4515', 'IS 5094', 'IS 9108', and 'IS 15466', were identified as drought tolerant and five accessions were sensitive to drought in both of the post‐rainy seasons. The tolerant accessions belonging to durra, caudatum, or durra‐caudatum races were of diverse geographical origins, and most yielded at par with or greater than the extensively grown cultivar 'IS 33844'. These accessions can be employed to investigate the physiological and molecular basis of drought adaptation and to breed for drought tolerance in sorghum.